The Lobster Lady - Hinrichs, Alexandra S. D., 1984-; Hogan, Jamie (Watertown, MA : Charlesbdridge, 2023)
"At 102-years-old, Virginia Oliver, or "The Lobster Lady," is the oldest person hauling lobster in Maine and possibly the world ; and she still remembers life as a little girl- -working along the rocky coast, enjoying time well spent with family"--
Ages 5-8.
Grades 2-3.
Keywords: Oliver, Virginia, -- 1920- -- Juvenile literature; Oliver, Virginia, -- 1920-; Lobster fishers -- Maine; Biography; Juvenile literature; Fishing villages -- Maine; Juvenile literature; Women -- Biography; Maine -- Biography; Juvenile literature; Maine -- Biography